Early modern knitted caps (fifteenth to sixteenth centuries): analyzing dyes in archaeological samples using microspectrofluorimetry complemented by HPLC–MS - Paula Nabais; Jane Malcolm-Davies; Maria João Melo; Natércia Teixeira; Beatrice Behlen (Heritage Science, 2023)
Abstract The knitted cap was the ubiquitous and most visible garment men wore throughout early modern society, from apprentices to royals. Documentary evidence also suggests that red was a conventional color for specific garments in the sixteenth century, including knitted caps. However, most knitted caps in museum collections are now a muddy brown characteristic of archaeological textiles, and their original color has seldom been studied. Considering the potential of microspectrofluorimetry for analyzing dyes in ancient textiles and manuscript illuminations, this technique was tested on six caps dating from the fifteenth to sixteenth centuries examined in the Knitting in Early Modern Europe research project. The colors are in good preservation condition in two samples, whereas the others show extensive degradation. The emission and excitation spectra acquired allowed the identification of the similarities and differences between samples, grouping them into different dye sources such as cochineal-based and madder-based (RED1 and RED2, respectively). For the coif cap and split-brimmed cap in good condition, analysis through HPLC–MS confirmed the sources of the dyes as Rubia tinctorum and cochineal. It also disclosed the source for another coif cap as Kermes vermilio (RED4). The other knitted items are possibly madder-based (RED3), but HPLC–MS did not allow confirmation of the madder source. The continuing development of a database of excitation and emission spectra acquired from historical textiles, such as the knitted caps, will support the identification of dye sources and specific formulations. Although this technique demands a comprehensive database of references for comparison with the complex signals identified, it allows for rapid spectra acquisition, providing tremendously valuable information.